If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -7 + -4y = 4y + -1 Reorder the terms: -7 + 7y + -4y = 4y + -1 Combine like terms: 7y + -4y = 3y -7 + 3y = 4y + -1 Reorder the terms: -7 + 3y = -1 + 4y Solving -7 + 3y = -1 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -7 + 3y + -4y = -1 + 4y + -4y Combine like terms: 3y + -4y = -1y -7 + -1y = -1 + 4y + -4y Combine like terms: 4y + -4y = 0 -7 + -1y = -1 + 0 -7 + -1y = -1 Add '7' to each side of the equation. -7 + 7 + -1y = -1 + 7 Combine like terms: -7 + 7 = 0 0 + -1y = -1 + 7 -1y = -1 + 7 Combine like terms: -1 + 7 = 6 -1y = 6 Divide each side by '-1'. y = -6 Simplifying y = -6
| 8a-6=3a+29 | | 6/8=15/4 | | (4/x+3)^-1 | | -1/5=x+2/5 | | (4x/9)^-3 | | 0.1*4200(23-18)/0.435(92-23)= | | 1/2(2x+4)+4x=4(9x/2+3x/4) | | 5(3x-2)+1-3(2x+1)=2(x+1) | | 25x+17=192 | | 28x=8*42 | | 7x+7=4x+58/7 | | (29b-1)-7(4b+3)=-7 | | 54-6c= | | -9z-5=-95 | | 10x+38=188 | | 17+5x=19+x | | 2(x+2)=2x-9 | | 4/5+z=3/4 | | 11+4(3x-1)=5(2x+1)+2(2x-5) | | 49x^2-42x+2=0 | | 12x^2+x+5=8 | | 12-y=2y+3 | | 4y=-8x-8 | | 3x=-11 | | -4y-2x=4 | | f*6-5=1 | | 262-6x=39x+17 | | -4y-2y=4 | | 1+4(2x-6)-3(x+4)=0 | | 6x+13=85 | | 3c-c= | | -4x-2y=4 |